Modern public finance - Herber, Bernard P. (Homewood, Ill. : R. D. Irwin, 1979)
This book attempts to provide a comprehensive and symmetrical framework for analyzing the influence of governmental revenue gathering and expenditure activities in all functional areas of economic activity. That is to say the framework of book focuses on the non-neutral economic effects, both positive and negative, that result from public sector fiscal (budgetary) decisions related to the allocation, distribution, and stabilization goals of society.
Includes bibliographical references and index.
ne 01/03/2018
Loans
Keywords: Finance, Public